Sensitivity and specificity of a single intradermal tuberculin test at the cervical and caudal folds in zabu cattle in Ethiopia - RAGASSA, ALEMAYEHU; AMENI, GOBENA (The Indian Journal of Animal Sciences, 2014)
Single intradermal tuberculin tests at cervical and caudal folds were evaluated on 107 zebu cattle at the same time. Test results were compared with detailed gross postmortem examination findings to estimate the sensitivity and specificity of the tests at the 2 sites. The sensitivity and specificity ofa single intradermal tuberculin test at the cervical fold ranged from 33.3 to 83.3%, and 79 to 95%, respectively, while those at the caudal fold ranged from 33.3 to 50%, and 94 to 99% respectively. The result indicated that the sensitivity of single tuberculin test at cervical fold is significantly (chi- square test, P <0.01) higher than the sensitivity at the caudal fold. The specificity of the test at the caudal fold is significantly (chi-square test, P <0.01) higher than the specificity at the cervical fold. Therefore, under Ethiopian condition, it is advantageous to use the caudal fold in intensive farms where the prevalence of the disease is high and the cervical fold in extensive farms where the disease prevalence is relatively lower.